Hypertensive Crisis in Pediatric Patients: An Overview - Raina, Rupesh; Mahajan, Zubin; Sharma, Aditya; Chakraborty, Ronith; Mahajan, Sarisha; Sethi, Sidharth K.; Kapur, Gaurav; Kaelber, David (Frontiers in Pediatrics, 2020)
Hypertensive crisis can be a source of morbidity and mortality in the pediatric population. While the epidemiology has been difficult to pinpoint, it is well-known that secondary causes of pediatric hypertension contribute to a greater incidence of hypertensive crisis in pediatrics. Hypertensive crisis may manifest with non-specific symptoms as well as distinct and acute symptoms in the presence of end-organ damage. Hypertensive emergency, the form of hypertensive crisis with end-organ damage, may present with more severe symptoms and lead to permanent organ damage. Thus, it is crucial to evaluate any pediatric patient suspected of hypertensive emergency with a thorough workup while acutely treating the elevated blood pressure in a gradual manner. Management of hypertensive crisis is chosen based on the presence of end-organ damage and can range from fast-acting intravenous medication to oral medication for less severe cases. Treatment of such demands a careful balance between decreasing blood pressure in a gradual manner while preventing damage end-organ damage. In special situations, protocols have been established for treatment of hypertensive crisis, such as in the presence of endocrinologic neoplasms, monogenic causes of hypertension, renal diseases, and cardiac disease. With the advent of telehealth, clinicians are further able to extend their reach of care to emergency settings and aid emergency medical service (EMS) providers in real time. In addition, further updates on the evolving topic of hypertension in the pediatric population and novel drug development continues to improve outcomes and efficiency in diagnosis and management of hypertension and consequent hypertensive crisis.